Effectiveness of Athlete Endorsements in Enhancing Brand Awareness: Insights from Nepal - Pokhrel, Pragyan (Nepalese Journal of Management Science and Research, 2026)
This study examines the impact of athlete endorsements on brand awareness in the Nepalese market, focusing on athlete credibility, athlete brand fit, athlete popularity, and frequency of endorsement. A quantitative research design was adopted, with data collected from 261 consumers across major urban areas using a structured questionnaire. Reliability analysis indicated high internal consistency, with an overall Cronbach’s alpha of 0.929 and individual variables ranging from 0.802 to 0.855. Correlation analysis revealed that all independent variables were positively and significantly associated with brand awareness, with frequency of endorsement (r = 0.792) and athlete popularity (r = 0.737) showing the strongest relationships. Regression analysis confirmed that these two factors significantly predict brand awareness, while credibility and brand fit were not statistically significant. The findings underscore the importance of using popular athletes and maintaining frequent endorsements to enhance brand visibility.